Dr. Seuss - MacDonald, Ruth K. (Boston : Twayne, 1988)
Appraises the work of children's author/illustrator Dr. Seuss.
Includes bibliographical references (p. 176-182) and index.
Young Adult.
Young Adult
Keywords: Seuss, -- Dr. -- Criticism and interpretation; Seuss, -- Dr. -- Criticism; Children's literature, American -- History and criticism; Children's literature -- History and criticism